An examination of the prevalence of khat chewing and its contributing factors among high school students in Addis Ababa, Ethiopia, using a cross-sectional survey design - Alembante Fikadu Lemma; Urban Robert; Lajtai Laszlo (International Journal of Africa Nursing Sciences)
Background: Khat (Catha edulis) is not just a substance but a cultural phenomenon in Ethiopia. This tiny tree induces euphoria by chewing its sensitive leaves and buds. It is grown in several locations in Ethiopia due to its high local and international demand. Khat is widely used for social and religious purposes, with users reporting a rise in spirit, sharper thinking, and vitality. Understanding the prevalence and factors associated with khat chewing among high school students in Addis Ababa is crucial for appreciating the cultural context and addressing the associated health issues. Methods: A rigorous cross-sectional design was employed, ensuring a comprehensive understanding of the current khat chewing situation among high school students in Addis Ababa. The study was conducted in Addis Ababa’s high schools, with 349 out of 529 students participating, a significant sample size. A simple random sampling technique was applied, enhancing the representativeness of the findings. A structured self-administered questionnaire was used, and descriptive and inferential statistics were applied to analyze the collected data, ensuring the reliability and validity of the results. Results: The prevalence of current khat chewing was 56.9 %. The fundamental reasons for current khat chewing were enjoyment, feeling better, overcoming bad moods or feelings, and feeling good while depressed or nervous. After conducting a multivariate logistic regression, the factors associated with current khat chewing behavior were Orthodox Christianity (AOR 0.62, 95 % CI: 0.17, 0.75), and Muslims (AOR 0.61, 95 % CI: 0.01, 0.96), students living with family members (AOR 1.96, 95 % CI: 0.22, 2.12), from urban areas (AOR 3.84, 95 % CI: 1.74, 8.50), with a monthly income of 2000 Ethiopian Birr (AOR 0.32, 95 % CI: 0.20, 0.51), students who study in Temenja Yazh High School (AOR 10.29, 95 % CI: 1.13, 93.29), who are in their 11th grade (AOR 2.62, 95 % CI: 1.25, 5.50), consumes 250 g or less of khat (AOR 7.54, 95 % CI: 2.17, 26.2), daily khat use (AOR 10.09, 95 % CI: 2.16, 47.10), spent 3 to 5 h (AOR 0.21, 95 % CI: 0.79, 0.60), and prefers 12:00–3:00 PM for chewing (AOR 0.09, 95 % CI: 0.02, 0.43). Conclusion: High school students in Addis Ababa, Ethiopia, reported using khat. Further research is needed to better understand how khat use affects academic achievement and health-related issues.